# 3x^2+3x=18

## Simple and best practice solution for 3x^2+3x=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3x^2+3x=18 equation:

Simplifying 3x^{2}+ 3x = 18 Reorder the terms: 3x + 3x^{2}= 18 Solving 3x + 3x^{2}= 18 Solving for variable 'x'. Reorder the terms: -18 + 3x + 3x^{2}= 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 3x + 3x^{2}= 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-6 + x + x^{2}) = 0 Factor a trinomial. 3((-3 + -1x)(2 + -1x)) = 0 Ignore the factor 3.## Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3## Subproblem 2

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2## Solution

x = {-3, 2}

### See similar equations:

| 12b^2+b-2(b^6+3b)= | | 2x+x^2=y | | x^2+4y=0 | | 12x^2=3 | | 56x=8x^2+98 | | 5x^2=16 | | 6x^2-3x=0 | | y=-2(5p^2+3p+1) | | y=-5a^3(2a^2+a-2b) | | y=-14b^3(14a+2a-5b^2) | | y=6ab^2(2a^2b-5ab-b^2) | | y=-a^5b^4(13a^4b^5-12ab^3+9ab^5) | | h(x)=7x^3-x^2+2 | | h=2x^1+-1x+7x^2 | | 16x^4-1=0 | | 15x^2-2=7x | | 7x^2=17x-6 | | 6x^3=26x^2+20x | | 2x^2-11=0 | | 3x^2+0.75x-1.5=0 | | 5x^2+8=18 | | 16-x^2=12 | | 200-x^2=100 | | 2x^2+13=15 | | (2x^2)-5x+6x-15=0 | | 2x^2=72 | | 112x-16x^2=0 | | 7-3X=8X^2 | | x^2-6x=0 | | x^2+2x-15=0 | | x^2-7x+12=0 | | x^2+x-6=0 | | x^2+13x+30=0 | | x^2+11x+28=0 | | x^2+4x+12=0 | | x^2+10x+21=0 | | x^2+2x-24=0 | | x^2-x-45=0 | | m^2+m-20=0 | | x^2+4x-32=0 | | p^2-p-30=0 | | x^2+6x+27=0 | | x^2+11x+24=0 | | x^2+8x+24=0 | | x^2+8x+16=0 | | x^2-7x-12=0 | | m^2+8m+12=0 | | 12x^4+7x^3+2x^2+7x-10=0 | | x^2+4x+11=14 | | 3t=r^2-28 | | 3t=t^2-28 | | 0=12x^2-1 | | 3x^2-12x+8=0 | | 3n^2+19=382 | | (6x^2+5x-15)+(10x+15)= | | X^2-9= | | (2x^2-6x+18)-(8x^2-11x-4)= | | (2x^2-6x+18)-(8x^2-11x-5)= | | -5x^5(-6x^4-10)= | | (8x^4-15x^3)-(-20x^4+13x^3)= | | (X-12)(x^2+2x-3)= | | ln(5)+x^2=6 | | 2y^2-10y+9=0 | | x^2+6x+8= | | c^2+8cd+15d^2= |